2014
DOI: 10.1120/jacmp.v15i6.4978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dosimetric misrepresentations from 3D conventional planning of liver SBRT using 4D deformable dose integration

Abstract: The purpose of this study is to evaluate dosimetric errors in 3D conventional planning of stereotactic body radiotherapy (SBRT) by using a 4D deformable image registration (DIR)‐based dose‐warping and integration technique. Respiratory‐correlated 4D CT image sets with 10 phases were acquired for four consecutive patients with five liver tumors. Average intensity projection (AIP) images were used to generate 3D conventional plans of SBRT. Quasi‐4D path‐integrated dose accumulation was performed over all 10 phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…9, and this process is similar to that from previous studies. 6,12) Fig. 10 shows the 3D dose distribution, 4D dose distribution, and the distribution of difference between the 3D and 4D dose, and this difference mainly occurred in the SI direction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9, and this process is similar to that from previous studies. 6,12) Fig. 10 shows the 3D dose distribution, 4D dose distribution, and the distribution of difference between the 3D and 4D dose, and this difference mainly occurred in the SI direction.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency of this difference was similar to that reported by a previous study using patient cases. 12) In further study, the effects of the factors that influence the difference between the 3D and 4D dose calculations, such as tumor size and motion, will be quantitatively analyzed using this phantom. Ultimately, the phantom could contribute to the discrimination of patients who would benefit from the 4D dose by estimating the condition of significant difference between the 3D dose and 4D dose according to the tumor size and motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 This deformable image registration-based approach revealed that conventional 3-dimensional (3D) planning approaches can significantly underestimate the dose to the planning target volume (PTV) in liver SBRT. 14 The purpose of this study is to investigate the impact of deformation on untargeted healthy organs and evaluate corresponding risk estimates in liver SBRT. Specifically, we demonstrate a methodology for assessing the risk of detriment using conventional 3D and 4D dose-warping approaches in terms of normal tissue complication probabilities 15,16 and latent risks of radiocarcinogenesis and cardiac complications.…”
Section: Introductionmentioning
confidence: 99%